Diversifying the Social Policy Curriculum: A Collaborative Approach. Issue 1 (January 2022) - Adewumi, Barbara; Mitton, Lavinia
Abstract : This article offers a practical methodological 'toolkit' for creating more diverse reading lists for social policy teaching. It reports on the findings of the award-winning 'Reading List Diversity Mark Project', carried out at the University of Kent in 2018–20, which investigated how many Black, Asian and other ethnic minority authors were included on undergraduate reading lists. Through the application of critical race theory (CRT), we argue that inclusive curricula matter. We then analyse the reasons for the marginalisation of race and ethnicity in the social policy curriculum. A distinctive aspect of the project was the nature of our staff-student collaboration and we discuss how this shaped its design and outcomes. We argue that our approach could be implemented at other institutions and conclude with suggestions about how to achieve a more diverse social policy curriculum.